Determinants and Growth Impact of Foreign Direct Investment in West African Economic and Monetary Union (1980-2010) - Laleye, Abimbola Nicaise (University of Lagos, 2015)
This study’s aim is to assess the trends and the macroeconomic determinants of FDI and to estimate its impact on economic growth, using West African Economic and Monetary Union (WAEMU) and its member countries (Benin, Burkina Faso, Cote d’Ivoire, Guinea Bissau, Mali, Niger, Senegal and Togo) as a case study. In order to achieve the objectives of the current study, the panel cointegration method is employed for the period that expands from 1980 to 2010. This method is constituted of three steps: first, running the panel unit root tests; secondly, run the panel cointegration tests to establish a long-run relationship between the included variables; and thirdly, to run the two models of this study. All this is supplemented by Granger causality test in order to determine the direction of causality between the two variables of FDI and economic growth in WAEMU and its member countries. The findings show that: (i) the variables market size, trade openness, human capital, infrastructure development, financial development, macroeconomic stability, exchange rate and political stability are significant determinants of FDI in WAEMU and in its member countries; (ii) not all the variables affect the same way FDI inflows in WAEMU and in each one of the WAEMU member countries; (iii) there is a positive relationship between FDI and economic growth which implies that FDI stimulates economic growth in WAEMU and its member countries; (iv) this study finds a causality relationship between FDI and economic growth, which runs from FDI to economic growth not from economic growth to FDI: meaning there is a unidirectional linkage between FDI and economic growth in WAEMU; (v) the study also finds that at cross-sectional level, FDI only causes economic growth, not the opposite: this implies that there is also a unidirectional linkage between FDI and economic growth in each WAEMU member country and its runs from FDI to economic growth. Therefore, it is important that the enabling environment should always be provided not only in WAEMU but also in its member countries in order to attract more foreign direct investment and further to stimulate the xiv country’s economic growth. Thus, this study recommends the followings, at the local or country level: first, improvement of the image of WAEMU countries. Rapid economic growth could result in an increase in foreign direct investment inflows, not only in WAEMU but in each one of the WAEMU member countries. But, this has to be done with more attention given to conditions (i.e. key variables) such as fair trade policy with abroad, development of infrastructure and financial system, availability of human capital through a sound human training and formation. At regional or WAEMU level, governments should set up policy that guaranties macroeconomic stability and political stability.
https://ir.unilag.edu.ng/handle/123456789/4079
Keywords: Co-integration; Determinants of FDI; FDI; Foreign direct investment; WAEMU; West African Economic and Monetary Union